Citizen Environmental Behavior From the Perspective of Psychological Distance Based on a Visual Analysis of Bibliometrics and Scientific Knowledge Mapping - Yang, Li; Fang, Xin; Zhu, Junqi (Frontiers in Psychology, 2022)
Global warming and other climate issues seriously threaten global sustainable development. As citizen environmental behavior can have a positive impact on the environment, it is of great theoretical significance and practical reference value to study the impact of psychological distance theory on citizen environmental behavior. This study obtained 2,339 related studies from 1980 to 2020 from the Web of Science as research objects, and used CiteSpace, VOSviewer, Netdraw, and other software programs to perform a bibliometric analysis. The results and conclusions are as follows. (1) The related research covered three periods: infancy, growth, and outbreak. (2) Chronologically, the relevant research evolved from building models to analyze the impact of environmental enrichment on human environmental behavior, to studying the motivation behind citizen environmental behavior, and finally to paying attention to sustainable development. (3) A cluster analysis of high-frequency keywords identified three research hotspots: "drivers of psychological distance of environmental change perception on citizen environmental behavior," "impact of social distance on adolescents' behavior," and "construal level theory and citizen green behavior." Based on these findings, possible future research directions were identified, including changing from a single theory to a combination of multiple theories to comprehensively study citizen environmental protection behavior; analyzing the motivation of citizen environmental behavior and summarizing the general motivation of environmental behavior according to its internal relationship; and determining how to narrow the global psychological distance, strengthen the awareness of the community of human destiny, and explore the establishment of an efficient global climate cooperation mechanism.